2013
DOI: 10.1002/jbm.a.34636
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis, characterization, and antimicrobial activity of cellulose–chitosan–hydroxyapatite composite material: A potential material for bone tissue engineering

Abstract: Hydroxyapatite (HAp) is often used as a bone-implant material because it is biocompatible and osteoconductive. However, HAp possesses poor rheological properties and it is inactive against disease-causing microbes. To improve these properties, we developed a green method to synthesize multifunctional composites containing: (1) cellulose (CEL) to impart mechanical strength; (2) chitosan (CS) to induce antibacterial activity thereby maintaining a microbe-free wound site; and (3) HAp. In this method, CS and CEL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 79 publications
(164 reference statements)
2
31
0
Order By: Relevance
“…The composites were tested for antibacterial activity on model bacterial strains E. coli (ATCC 8739), Staphylococcus aureus (ATCC 25923), methicillin resistant S. aureus (ATCC 33591), vancomycin resistant Enterococcus faecalis (ATCC 51299), and Pseudomonas aeruginosa (ATCC 9027) using previously published protocol (Harkins et al, 2014; Mututuvari et al, 2013; Tran et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composites were tested for antibacterial activity on model bacterial strains E. coli (ATCC 8739), Staphylococcus aureus (ATCC 25923), methicillin resistant S. aureus (ATCC 33591), vancomycin resistant Enterococcus faecalis (ATCC 51299), and Pseudomonas aeruginosa (ATCC 9027) using previously published protocol (Harkins et al, 2014; Mututuvari et al, 2013; Tran et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated recently that a simple ionic liquid, butylmethylimmidazolium chloride ([BMIm + Cl − ]), can dissolve polysaccharides such as CEL and chitosan (CS), and by use of this [BMIm + Cl − ] as the sole solvent, we developed a simple, green and totally recyclable method to synthesize [CEL+CS] composites just by dissolution without using any chemical modifications or reactions (Duri & Tran, 2013; Harkins et al, 2014; Mututuvari & Tran, 2013; Mututuvari & Tran, 2014; Tran et al, 2013a; Tran et al, 2013b). The [CEL+CS] composite obtained was found to be not only biodegradable and biocompatible but also retain unique properties of its components.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed the potential use of (CEL + CS + HA) composites as scaffolds in bone tissue engineering (Mututuvari, Harkins, & Tran, 2013). Hydroxyapatite (HA) was subsequently formed in situ by alternately soaking (CEL + CS) composites in aqueous solutions of CaCl 2 and Na 2 HPO 4 .…”
Section: Applications Of Chitin and Chitosan For Bone Tissue Engineeringmentioning
confidence: 96%
“…In these cases, generally, the antimicrobial agent is either absorbed or impregnated in the CaP matrix and then its interaction with microbes and host tissues is studied. 34 Melo et al synthesized antimicrobial dental adhesives based on nanoparticles of Ag and ACP. 32 In a similar kind of work, Ciobanu et al synthesized Ag doped HAp by co-precipitation and reported high antibacterial activity towards Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%